Effects of the dopamine transporter gene on neuroimaging findings in different attention deficit hyperactivity disorder presentations - Bacanli, Ali; Unsel-Bolat, Gul; Suren, Serkan; Yazici, Kemal Utku; Calli, Cem; Jafari, Duygu Aygunes; Ercan, Eyup Sabri (Springer, 2021)
Attention-Deficit/Hyperactivity Disorder (ADHD) is a phenotipically and neurobiologically heterogeneous disorder. Deficiencies at different levels in response inhibition, differences in dopamine transporter genotype (DAT1) and various symptomatic presentations contribute to ADHD heterogeneity. Integrating these three aspects into a functional neuroimaging research could help unreval specific neurobiological components of more phenotipically homogeneous groups of patients with ADHD. During the Go-NoGo trial, we investigated the effect of the DAT1 gene using 3 T MRI in 72 ADHD cases and 24 (TD) controls that typically developed between the ages 8 and 15 years. In the total ADHD group, DAT1 predicted homozygosity for the 10R allele and hypoactivation in the anterior cingulate cortex and paracingulate cortex. There were no significant activation differences between DAT1 10R/10R homozygotes and 9R carriers in TD controls. Subjects with predominantly inattentive ADHD (ADHD-I) presentation with DAT1 10R/10R homozygous reduced neuronal activation during Go trial particularly in the frontal regions and insular cortex, and in the parietal regions during NoGo trial (brain regions reported as part of Default Mode Network- DMN). Additionally, DAT1 10R/10R homozygousness was associated with increased occipital zone activation during only the Go trial in the ADHD combined presentation (ADHD-C) group. Our results point the three main findings: 1) The DAT1 gene is 10R homozygous for differentiated brain activation in ADHD cases but not in the TD controls, supporting the DAT1 gene as a potential marker for ADHD, 2) The relationship between the DAT1 gene and the occipital regions in ADHD-C group which may reflect compensatory mechanisms, 3) The relationship between DAT1 gene and the reduced DMN suppression for 9R carriers probabaly stems from the ADHD-I group.
Keywords: Attention-deficit; hyperactivity disorder; ADHD subtypes; DAT1 gene; fMRI; Neuroimaging genetic